2002
DOI: 10.1039/b202769k
|View full text |Cite
|
Sign up to set email alerts
|

Direct visualization of layer-by-layer self-assembled multilayers of organometallic polymers

Abstract: Direct visualization of organometallic-organic and novel all-organometallic multilayer superlattices prepared by layer-by-layer assembly of cationic/anionic polyferrocenylsilane and anionic polystyrene sulfonate polyelectrolytes using a gold coating/transmission electron microscopy (TEM) technique is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 15 publications
5
27
0
Order By: Relevance
“…Characterization of PFS multilayers by TEM may allow the effect of polymer structure, composition and charge density on thin film thicknesses to be established. Figure 7 gives an example of TEM images for the cross-section of an organic-PFS hybrid multilayer (composed of PFS polycation 5 and PSS) and a full PFS multilayer (composed of PFS polycation 5 and polyanion 10) [38].…”
Section: Multilayer Formation and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Characterization of PFS multilayers by TEM may allow the effect of polymer structure, composition and charge density on thin film thicknesses to be established. Figure 7 gives an example of TEM images for the cross-section of an organic-PFS hybrid multilayer (composed of PFS polycation 5 and PSS) and a full PFS multilayer (composed of PFS polycation 5 and polyanion 10) [38].…”
Section: Multilayer Formation and Characterizationmentioning
confidence: 99%
“…The successful exploration of these hybrid multilayer thin films was soon extended to the fabrication of fully organometallic superlattices solely composed of PFS polyelectrolytes. Multilayers were deposited on (but are not restricted to) quartz slides, silicon wafers, gold substrates, and quartz crystal microbalance substrates [36][37][38]. For gold substrates, normally a predeposited thiol monolayer (such as sodium 3-mercapto-1-propanesulfonate, 11-mercaptoundecanoic acid, or 2-aminoethanethiol hydrochloride) was applied to impart negative or positive charges to the surfaces.…”
Section: Multilayer Formation and Characterizationmentioning
confidence: 99%
“…[201][202][203][204][205][206] A number of water-soluble poly(ferrocenylsilanes) and polyelectrolytes have also been produced by side-chain functionalization. [207][208][209][210][211][212][213][214] Scheme 50 shows the synthesis of water-soluble anionic (153) and cationic (155) polyelectrolytes. [212] Pannell and coworkers have reported the use of poly(ferrocenylsilane) homo-and copolymers as coatings for tapered optical-fiber gas sensors of NH 3 , CO 2 and N 2 O.…”
Section: Ring-opening Polymerizationmentioning
confidence: 99%
“…[289,290] In 1988, Macomber and coworkers reported the synthesis of an unsaturated tungsten-carbene complex that underwent polymerization upon standing under a nitrogen atmosphere at 10 8C for 7 d (Scheme 67). [289] The resulting polymer (211) was insoluble in all organic solvents tested, however its structure was identified by IR, solid-state NMR and Xray photoelectron spectroscopies. If this polymer was placed in DMSO for 4 d at 25 8C, a copolymer (212) containing metal-carbene methyl acrylate units was isolated.…”
Section: Scheme 63mentioning
confidence: 99%
“…174,175 The polyions were deposited electrostatically onto a variety of substrates, such as silicon, gold, and hydrophilic/hydrophobically patterned substrates, the latter of which led to the formation of laterally structured PFS multilayers. 176 It was reported that hydroxyl-terminated monolayer alkanethiol regions prevented deposition of the polyions due to hydrogen-bonding interactions with the solvent.…”
Section: Layer-by-layer Assembly Of Water-soluble Polyferrocenylsilanmentioning
confidence: 99%